2020
DOI: 10.1101/2020.07.22.214791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cytochrome OmcS is not essential for long-range electron transport inGeobacter sulfurreducensstrain KN400

Abstract: The multi-heme c-type cytochrome OmcS, is one of the central components for extracellular electron transport in Geobacter sulfurreducens strain DL-1, but its role in other microbes, including other strains of G. sulfurreducens is currently a matter of debate. Therefore, we investigated the function of OmcS in G. sulfurreducens strain KN400, which is even more effective in extracellular electron transfer than strain DL-1. We found that deleting omcS from strain KN400 did not negatively impact the rate of Fe(III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Furthermore, deleting omcS has no negative impact on biofilm conductivity or current production ( 15 , 31 ). Deletion of omcS can inhibit Fe(III) oxide reduction, in some, but not all variants of G. sulfurreducens ( 32 , 33 ). When deletion of omcS does have an impact, the strain can be rescued for Fe(III) oxide reduction with the addition of ultrafine-grained magnetite ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, deleting omcS has no negative impact on biofilm conductivity or current production ( 15 , 31 ). Deletion of omcS can inhibit Fe(III) oxide reduction, in some, but not all variants of G. sulfurreducens ( 32 , 33 ). When deletion of omcS does have an impact, the strain can be rescued for Fe(III) oxide reduction with the addition of ultrafine-grained magnetite ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…G. sulfurreducens strain Aro-5 cannot produce highly conductive biofilms or high current densities on anodes (18), whereas deleting omcS has no impact on these phenotypes (17, 29). Deletion of omcS can inhibit Fe(III) oxide reduction, in some, but not all variants of G. sulfurreducens (30, 31). When deletion of omcS does have an impact, the strain can be rescued for Fe(III) oxide reduction with the addition of ultrafine-grained magnetite (32).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, OmcS facilitates direct contact with the solid extracellular electron donors and acceptors. However, it was shown that G. sulfurreducens strain KN400 did not require OmcS for DIET and Fe(III) oxide reduction, indicating that the requirement of OmcS for EET is strain specific (85).…”
Section: Outer Membranementioning
confidence: 99%